1981
DOI: 10.1002/jmv.1890080407
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features in chronic non‐A, non‐B (NANB) hepatitis: A controlled blind study

Abstract: Liver biopsies from 12 patients with chronic Non-A, Non-B (NANB) hepatitis, 7 with hepatitis B surface antigen (HBsAg) positive chronic liver disease, 1 HBsAg positive normal carrier, and 4 patients with non-viral liver disease, were examined by electron microscopy for cytoplasmic and nuclear changes. Aggregates of particles measuring 20-35 nm in diameter were noted in the nuclei of 8 of 12 patients with NANB chronic hepatitis, but not in the other groups. The tubular changes seen in the endoplasmic reticulum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The findings of the Leuven group (20), which we have confirmed, suggest that this change is associated, as it is in chimpanzees, with characteristic nuclear particles which seem not to be virus. Similar electron microscopic nuclear alterations have been found in several other studies in man (27)(28)(29)(30). The tubular cytoplasmic lesion observed in chimpanzees (3 1) has thus far been noted only by few observers (30, 32) in man.…”
Section: Discussionsupporting
confidence: 80%
“…The findings of the Leuven group (20), which we have confirmed, suggest that this change is associated, as it is in chimpanzees, with characteristic nuclear particles which seem not to be virus. Similar electron microscopic nuclear alterations have been found in several other studies in man (27)(28)(29)(30). The tubular cytoplasmic lesion observed in chimpanzees (3 1) has thus far been noted only by few observers (30, 32) in man.…”
Section: Discussionsupporting
confidence: 80%
“…Circular cytoplasmic structures resulting from apposition of two cisternae of endoplasmic reticulum have also been described by Busachi et a1 [1981] in liver biopsies from patients with chronic non-A, non-B hepatitis, but it was emphasized that the typical tubular structures found in chimpanzees were not observed in any of their patients. In other studies, cytoplasmic tubular structures were not detected in hepatocytes of patients with non-A, non-B hepatitis [Gmelin et al, 1980;Bamber et al, 1981;Cabral et al, 1981;Gibo et al, 1982;Kunze et al, 19821. However, cytoplasmic tubular alterations similar to those observed in chimpanzees with non-A, non-B hepatitis have been found in lymph nodes, lymphocytes, monocytes, and tissue macrophages of patients with the acquired immune deficiency syndrome [Sidhu et al, 1983;Schaf et al, 1983;Orenstein, 1983;Ewing et at, 19831 and in circulating lymphocytes and lymph nodes of patients with persistent lymphadenopathy and the acquired immune deficiency syndrome [Anderson et al, 19841. Several laboratories have also reported virus-like particles in liver biopsies of patients with non-A, non-B hepatitis.…”
Section: Introductionmentioning
confidence: 92%
“…The assumption that the patient suffered from a simultaneous infection by NANB agents and HBV was supported by findings on the electron microscopic level. In the same specimen core particles of the HBVand aggregates of nuclear particles regarded as characteristic for human NANBH (9,11,12,13,14) could be demonstrated in separate liver cells. The specificity of these nuclear inclusions with a diameter of 20-27 nm, however, has recently been questioned by investigators who found them in tumors of non-hepatic origin (15).…”
Section: Discussionmentioning
confidence: 83%